Effect of sperm selection method by cumulus oophorus complexes and conventional sperm preparation method on sperm quality and DNA fragmentation for assisted reproduction techonology. (December 2019) - Naknam, Wasin; Salang, Lingling; Sothornwit, Jen; Amnatbuddee, Siriruthai; Seejorn, Kanok; Pongsritasana, Thanida; Sukkasame, Sineenart
Abstract: Objectives: To compare the effectiveness of sperm selection using cumulus oophorus complexes (COCs) and conventional sperm preparation methods on sperm quality and DNA fragmentation Methods: Normal semen samples under the World Health Organization (WHO)'s 2010 eligibility criteria were collected and processed using conventional sperm preparation methods. The prepared sperm were divided into two groups. Spermatozoa in the study group were selected based on their ability to penetrate a layer of COCs. In the control group, spermatozoa were kept in culture medium under similar conditions. The selected-sperm were evaluated based on sperm quality and DNA fragmentation. Results: Thirty normal semen samples were recruited. Spermatozoa that were able to passthrough the COCs had significantly higher sperm motility parameters than the control group (curvilinear velocity [VCL; 143.5 vs 122.2; P < 0.01], average path velocity [VAP; 83.6 vs 69.3; P < 0.01], straight-line velocity [VSL; 67.95 vs 60.45; P < 0.01]). The percentage of normal spermatozoa morphology in the COCs group was significantly higher than in the control group (21.70% vs 18.76%). In addition, there was significantly less DNA fragmentation in the COCs group than in the control group (18.83 vs 10.83). Conclusion: Spermatozoa selected using COCs were likely to be effective in terms of sperm quality and DNA fragmentation.